The Systematic Undoing of Pollution Solutions - Garcia, Christopher (The Toro Historical Review, 2023)
The growing understanding of environmental cosnequences led to positive movements as an attempt to slow down and resolve the negative impacts. These movements drew in a lot of support and saw progress being made. This progress saw backlash as goveremnt policies were not too beneficial to some industries. The following decade saw the reversal of the positve changes and the negative impacts increased.